2021
DOI: 10.1039/d1ra00454a
|View full text |Cite
|
Sign up to set email alerts
|

Conductive nanosheets produced by UV irradiation of a Ag nanoparticle monolayer at the air–water interface

Abstract: UV irradiation of Ag NPs spreading on water results in the formation of large Ag NPs, but the solubilization of adequate additives in water, such as EDTA and PVP, leads to conversion to a transparent conductive film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The mesh-like structure in this study was very similar to that of a previously reported Langmuir AuNP monolayer, 24,25 although the mesh-like nanosheet of the Langmuir system in the previous study was obtained via the transformation of a flat nanosheet produced directly from the AuNP monolayer. The difference in the morphology of the nanosheets may stem from the density of the AuNPs on the water surface.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…The mesh-like structure in this study was very similar to that of a previously reported Langmuir AuNP monolayer, 24,25 although the mesh-like nanosheet of the Langmuir system in the previous study was obtained via the transformation of a flat nanosheet produced directly from the AuNP monolayer. The difference in the morphology of the nanosheets may stem from the density of the AuNPs on the water surface.…”
Section: Resultssupporting
confidence: 84%
“…This suggested that prolongated UV irradiation led to the progress of fusion, consequently causing the AuNPs to form a fine mesh-like nanosheet. In previous papers, , we demonstrated that Au nanosheets can be prepared from Langmuir monolayer of dodecanethiol capped AuNPs, and the capping molecules had little influence on the morphology of UV irradiated products. Accordingly, when adsorbed AuNP monolayers prepared by the other suitable surfactants are subjected to UV irradiation, it is naturally expected that similar mash-like Au nanosheets will be obtained.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…To overcome this problem, we used the water surface as an alternative substrate. Specifically, PS films at air–water interfaces were subjected to UV-irradiation-assisted patterning; the patterned PS films were found to stick to various substrates, including curved ones, without any peeling process, providing further postprocessing opportunities for the construction of more complex and elaborate nanopatterns. By focusing the UV light, photoreactive products can be deposited in small areas by simply solubilizing photoreactive compounds in the water phase, which is another advantage of a water surface as the processing substrate (Figure C). Herein, we report the use of an aqueous solution of silver ions (as the photoreactive compound) to fabricate periodic spot arrays of Ag nanoparticle aggregates on PS films.…”
Section: Introductionmentioning
confidence: 99%